Developmental Profile of Infants Visiting the Growth and Development Clinic, Child Health Department, Medical School, Padjadjaran University - Prihariadi R. Poedjiadi; Sri Indayati Soewaryo; Ponpon Ijradinata (Indonesian Pediatric Society, 1999)
Development of a child is the result of a continuous interaction betweenbiological factor serving as basis and the environment that gives stimulation. Indonesia as a developing country has an environmental characteristically different from that of advanced countries such as USA, where the Bayley developmental test tool was constructed, so that as an initial step in order to find out how far the level of development of the Indonesian child in general was, a study was made on the level oldevelopmental of healthy 18-month-old infants visiting the Growth & Development Clinic in the Child Health Department of Dr. Hasan Sadikin General Hospital Bandung. Thirty healthy infants were chosen comprising 19 (63%) male and 11 (37%) female infants who were born nonnally without any congenital deviation, with good nutritional status, not anemic, never been hospitalized and had a good physical status during the study period. This study yielded an average Index of Mental Development(IPM) of 124.2 (6.94) and an index of Psychomotor Development (IPP) of 110.7 (6.16). The resulting IPM and IPP were higher compared to the notmal Bayley scale for 18-month-old infants (p<0.0001). This could be due to the absence of several biological risk factors in the subjects and to the sullicient amount of a ttention given by all members of the family so that the child developed well.